Whole-genome analysis suggesting probiotic potential and safety properties of Pediococcus pentosaceus DSPZPP1, a promising LAB strain isolated from traditional fermented sausages of the Basilicata region (Southern Italy) - Tathode, Madhura S.; Bonomo, Maria Grazia; Zappavigna, Silvia; Mang, Stefania Mirela; Bocchetti, Marco; Camele, Ippolito; Caraglia, Michele; Salzano, Giovanni (Frontiers in Microbiology, 2024)
Introduction Many lactic acid bacteria (LAB) strains are currently gaining attention in the food industry and various biological applications because of their harmless and functional properties. Given the growing consumer demand for safe food, further research into potential probiotic bacteria is beneficial. Therefore, we aimed to characterize Pediococcus pentosaceus DSPZPP1, a LAB strain isolated from traditional fermented sausages from the Basilicata region of Southern Italy. Methods In this study, we analyzed the whole genome of the P. pentosaceus DSPZPP1 strain and performed in silico characterization to evaluate its applicability for probiotics and use in the food industry. Results and Discussion The whole-genome assembly and functional annotations revealed many interesting characteristics of the DSPZPP1 strain. Sequencing raw reads were assembled into a draft genome of size 1,891,398 bp, with a G + C content of 37.3%. Functional annotation identified 1930 protein-encoding genes and 58 RNAs including tRNA, tmRNA, and 16S, 23S, and 5S rRNAs. The analysis shows the presence of genes that encode water-soluble B-group vitamins such as biotin, folate, coenzyme A, and riboflavin. Furthermore, the analysis revealed that the DSPZPP1 strain can synthesize class II bacteriocin, penocin A, adding importance to the food industry for bio-enriched food. The DSPZPP1 genome does not show the presence of plasmids, and no genes associated with antimicrobial resistance and virulence were found. In addition, two intact bacteriophages were identified. Importantly, the lowest probability value in pathogenicity analysis indicates that this strain is non-pathogenic to humans. 16 s rRNA-based phylogenetic analysis and comparative analysis based on ANI and Tetra reveal that the DSPZPP1 strain shares the closest evolutionary relationship with P. pentosaceus DSM 20336 and other Pediococcus strains. Analysis of carbohydrate active enzymes (CAZymes) identified glycosyl transferases (GT) as a main class of enzymes followed by glycoside hydrolases (GH). Our study shows several interesting characteristics of the isolated DSPZPP1 strain from fermented Italian sausages, suggesting its potential use as a promising probiotic candidate and making it more appropriate for selection as a future additive in biopreservation.